'You have got to stick to your times': Care workers and managers' experiences of working in extra care housing. (20th October 2019) - Cameron, Ailsa; Johnson, Eleanor K.; Evans, Simon; Lloyd, Liz; Darton, Robin; Smith, Randall; Porteus, Jeremy; Atkinson, Teresa
Abstract: Extra care housing (ECH) has been lauded as an innovative model of housing with care for older people that promotes and supports independent living. The study used a qualitative design to explore how care is delivered in four extra care settings in England over 20 months during 2016–2017. This paper reports findings from semi‐structured interviews with 20 care workers and seven managers. The article argues that, despite being heralded as a new model, care workers in ECH face similar organisational pressures as those working in more conventional settings and, in turn, the care which they are able to provide to residents mimics traditional forms of care.